Evaluation of Public Buildings as Tsunami Evacuation Vertical Based on Tsunami History - Soviana, Widya; Zein, Keumala Citra Sarina; Abidin, Zainal; Ramadhan, Misbahul (Semesta Teknika, 2024)
The research method was carried out through a survey of a number of buildings in the coastal area of Banda Aceh City. The analysis was carried out by comparing the floor heights of buildings with the historical height of the tsunami that occurred in 2004. Based on the survey results, it was found that there were 319 public buildings spread across the coastal area of Banda Aceh City. The percentage of each is known by the number of government office buildings (31.7%), educational facilities (40.8%), health services (5.6%), places of worship (16.6%), trade (2.2%), and other facilities (3.1%). From the analysis of building floor heights, a total of 194 buildings, or 60.81% of the total existing public buildings could function as alternative vertical evacuation sites for the tsunami disaster. This amount can accommodate 43.95% of the total population living in the surrounding area. Thus, part of the population can carry out vertical disaster evacuation. While others are planned through horizontal evacuation scenarios. Public buildings designated as vertical evacuation sites are only calculated from the safe height of the building floor. In contrast, in terms of the resilience of the building structure, it can be re-evaluated.